Evaluación de la Calidad de Vida post amputación traumática de miembros inferiores. - Sevilla Tapia, Domenica Sofia (2024)
Traumatic lower limb amputations constitute processes that considerably affect all aspects of the lives of the affected people. This situation's implication affects patients' physical, psychological, and social integration. The objective of this research was to carry out a bibliographic review to obtain updated information on the evaluation of quality of life after traumatic lower limb amputation. An essential, documentary, descriptive, and transversal research consisting of a non- systematic bibliographic review of documents published in the last ten years was carried out. The universe consisted of a total of 97 papers; Of them, 43 were part of the study sample. The information was collected in regional (Latindex, Lilacs, Scielo, and Redalyc) and high-impact databases (Scopus, Medline, PubMed, and Ice Web of Science). Boolean operators and health descriptors were used to optimize the search for information. The main results include the determination of the risk factors associated with traumatic lower limb amputations, the description of the elements related to the psychological affectation faced by patients, and the identification of the main factors that influence patients' perceptions of quality of life. Post-traumatic lower limb amputation patients. It is concluded that traumatic amputation of lower limbs causes a decrease in the perception of the quality of life of patients, generating physical, psychological, and social incorporation effects.